The economics of imperfect labor markets - Boeri, Tito; Ours, J. C. van (Princeton : Princeton University Press, 2021)
'The leading textbook on imperfect labor markets and the institutions that affect them-now completely updated and expanded'--
Includes bibliographical references and index.
Buku bacaan asas prasiswazah Fakulti Ekonomi Pengurusan 2023/24.
Keywords: Labor market